Myeloid-Derived Suppressor Cells as Target of Phosphodiesterase-5 Inhibitors in Host-Directed Therapeutics for Tuberculosis - Leukes, Vinzeigh; Walzl, Gerhard; du Plessis, Nelita (Frontiers in Immunology, 2020)
Resistance towards current and new classes of anti-tuberculosis (TB) antibiotics are emerging rapidly, thus innovative therapies focussed on host processes, termed host- directed-therapy (HDT), are promising novel approaches for shortening therapy regimens without inducing drug resistance. Development of new TB drugs is lengthy, expensive, and success is not guaranteed, thus alternatives are needed. Repurposed drugs have already passed FDA/EMA safety requirements and may only need to prove efficacy against Mycobacterium tuberculosis (M.tb). Phosphodiesterases (PDE), hydrolyse the catalytic breakdown of both cAMP and cyclic 3′, 5′ guanosine monophosphate (cGMP), to their inactive mononucleotides. Advances in molecular pharmacology have identified 11 PDE families and the success of sildenafil, a PDE5 selective inhibitor (PDE-5i), in treating pulmonary hypertension and erectile dysfunction has invigorated research into the therapeutic potential of selective PDE inhibitors in other conditions. Myeloid-Derived Suppressor Cells (MDSC) suppress anti-TB T cell responses, likely contributing to TB disease progression1–3. PDE-5i increase cGMP within MDSC resulting in downregulation of ARG1 and NOS2, reducing MDSC suppressive potential4. The effect of this reduction decreases MDSC-induced T cell suppressive mechanisms4. This review highlights the possibility of HDT targeting of MDSC, using PDE-5i in combination with the drug-sensitive (ds) TB regimen, resulting in improved TB treatment efficacy.